Phylogenetic and Taxonomic Status Analyses of the Abaso Section from Multiple Nuclear Genes and Plastid Fragments Reveal New Insights into the North America Origin of Populus (Salicaceae) - Liu, Xia; Wang, Zhaoshan; Shao, Wenhao; Ye, Zhanyang; Zhang, Jianguo (Frontiers in Plant Science, 2017)
Although, the Abaso section is widely accepted as an independent section, the taxonomic status of Populus mexicana (section Abaso) has not yet been resolved due to the limited availability markers and/or the lack of P. mexicana specimens in previous studies. Thirty-one poplar species that represent six sections of the Populus genus were sampled, and 23 single-copy nuclear DNA and 34 chloroplast fragments were sequenced. The present study obtained two updated phylogenies of Populus. We found that monophyly of the genus Populus is strongly supported by nuclear and plastid gene, which is consistent with previous studies. P. mexicana, diverged first in the nuclear DNA tree, which occupied the basal position, implying that the section Abaso may be the most ancestral lineage in extant populous species. Given that the short branches and low statistical support for the divergence of sections Abaso and Turanga, this observation probably indicated that a rapid radiation evolution following the early split of the genus Populus. In the plastid tree, P. mexicana clustered with modern-day species of section Tacamahaca in the plastid tree. Based on cytoplasmic and single-copy nuclear marker sequences, we hypothesized that chloroplast capture resulted in the inconsistent position of P. mexicana between the phylogenetic trees. Given the first unequivocal records of poplar fossils from the Eocene with similar leaf morphology to the extant P. mexicana and the phylogenetic positions of P. mexicana in our study, we support the hypothesis that the Populus genus originated in North America, which will provide new insights to the development of the origin of Populus species.